2022
DOI: 10.1186/s12913-022-08652-5
|View full text |Cite
|
Sign up to set email alerts
|

Do patients want clinicians to ask about social needs and include this information in their medical record?

Abstract: Background Social needs screening in primary care may be valuable for addressing non-medical health-related factors, such as housing insecurity, that interfere with optimal medical care. Yet it is unclear if patients welcome such screening and how comfortable they are having this information included in electronic health records (EHR). Objective To assess patient attitudes toward inclusion of social needs information in the EHR and key correlates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Interviews and patient expert feedback found that patient–care team communication is crucial for screener uptake. Sensitive questions about patient needs may lead to incomplete or untruthful responses if patients have privacy concerns, 10 , 23 feel embarrassed, or fear stigmatization. 24 Patient experts and health care team members emphasized rapport building and communicating the screening purpose to mitigate patient concerns and build trust.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews and patient expert feedback found that patient–care team communication is crucial for screener uptake. Sensitive questions about patient needs may lead to incomplete or untruthful responses if patients have privacy concerns, 10 , 23 feel embarrassed, or fear stigmatization. 24 Patient experts and health care team members emphasized rapport building and communicating the screening purpose to mitigate patient concerns and build trust.…”
Section: Discussionmentioning
confidence: 99%
“…These complemented and expanded the individual-level SDoH data (food/housing security, transportation, interpersonal violence, etc.) captured directly in EHRs [25,26,28,46,73,82,84,[87][88][89][90][91][92][93].…”
Section: Longitudinal Study Data Included the National Longitudinal S...mentioning
confidence: 99%
“…Participants completed the survey on a computer tablet before, during, or after their clinic visit. The survey consisted of the 10-item Accountable Health Communities (AHC) healthrelated social needs screening tool, 38,39 which is widely used 28,[40][41][42][43][44] and includes questions on housing, food, transportation, utilities, and interpersonal violence; 2 outcome measures of acceptability; and 20 questions on social risk factors associated with patient acceptability (eAppendix in Supplement 1). We modified questions from an earlier study evaluating acceptability of social risk screening in primary care clinics and EDs 28,45 for use in a dermatology clinic setting.…”
Section: Quantitative Component: Procedures Measures and Outcomesmentioning
confidence: 99%